OTHERNESS IN CULTURE AND THE INDIVIDUAL, THROUGH THE PRISM OF THE FILM “UNDER THE SKIN” (Journal of Contemporary Philology, 2023)
This paper analyzes the expression of otherness as interpreted by modern philosophers and thinkers of, such as Emmanuel Levinas, Jean-Paul Sartre, Simone de Beauvoir through the prism of the film Under the Skin (2013). This paper will explore how otherness is expressed in the movie, be it from the position of the alien towards the human and of the human towards the alien, the implications this has for cultures and individuals living in a society, as well as possible hypotheses about how this process of othering can be overcome for the sake of a more open and accepting society, based on feminist and post-humanist ideas and philosophers such as Donna Haraway. We will see how by interpreting the movie through philosophical and culturological concepts, we can discover numerous ways through which the film can be understood to comment on social problems and dilemmas, on gender phenomena, immigration, the subaltern, the gaze, anthropocentrism and various topics of importance for contemporary philosophical and cultural thinking.
Keywords: feminism; post-humanism; cultural interpretation; anthropocentrism; the Оther